Evaluación de Cultivares de Ajo Morado y Blanco por su Rendimiento Agronómico e Industrial en Irapuato, Guanajuato. - Pérez Moreno, Luis; García Rincón, Paulo Manuel; Ramírez Malagón, Rafael; Barrera Guerra, José Luis (Acta Universitaria, 2003)
Field yield, bulb quality, and industrial yield of garlic (Allium sativum L.) cultivars were evaluated during the 1988-1989, 1989-1990, 1991-1992 and 2001-2002 fall-winter cycles at the Institute of Agricultural Sciences of the University of Guanajuato. Purple and white color bulb varieties were evaluated with variable results, depending on the genotype and vegetative cycle. None of the short life cycle cultivars qualified for field or industrial yield and bulb quality. Best field yields, higher weight per bulb and smaller clove number per bulb were obtained with: Cristal, Chileno Compuesto No. 1, and Taiwán. For industrial yield (t ha-1dehydrated garlic), the best cultivars were Cristal, Pocitas, Hermosillo, and Napuri. It is important to continue with the program of garlic genetic breeding, based on selection of new garlic lines derived from the best genotypes and using techniques as the virus elimination for improving yield and quality.